Effect of Oral Prednisolone on Recovery after Tonsillectomy: A Quasi-Experimental Study - Amatya, Paras Raj; Chettri, Shyam Thapa; Sah, Bajarang Prasad; Kandel, Dillu Ram (Journal of BP Koirala Institute of Health Sciences, 2023)
Background: Post-operative morbidities following tonsillectomy still remain a significant problem. Glucocorticoids might help to lessen these morbidities by decreasing inflammation at the sites of injury. The objective of this study was to assess the effect of oral prednisolone on recovery of patients after tonsillectomy. Methods: A quasi-experimental study was conducted from August 2015 to July 2016 among 70 patients aged four years or older scheduled for elective tonsillectomy by cold steel dissection method. The experimental group received a postoperative course of prednisolone 0.5 mg/ kg/ day over seven days whereas the control group received the standard of care only. Postoperatively, all participants were assessed for pain, type of diet and activity, presence of nausea and/ or vomiting and bleeding on 1st , 2nd , 3rd, 7th and 14th day, and healing process in the tonsillectomy bed measured through the use of endoscopic photograph on 7th and 14th day. Results: Significant reduction in pain was found in prednisolone group compared to the control group on 7 th day (mean score 1.41 and 2.51 respectively, p = 0.006) and on 14 th day (mean score 0.25 and 1.06 respectively, p = 0.005). Earlier return to normal diet was found on 7th day (p = 0.005) and 14th day (p = 0.02). No significant difference was found in rate of healing and other secondary outcomes. No adverse effects of prednisolone were noted. Conclusion: Use of oral prednisolone in post-tonsillectomy patients may offer significant benefits in relieving pain and earlier returning to normal diet without any serious adverse effects.